Preparation and characterization of sodium polyacrylate-grafted bentonite and its performance removing Pb2+ from aqueous solutions. Issue 101 (18th October 2016) - Xue, Ni; Wang, Luyan; Pei, Meishan; He, Youjun; Du, Yankai; Guo, Wenjuan
Abstract : A new adsorbent, sodium polyacrylate (PAANa) grafted onto the surface of bentonite (Bent), was successfully synthesized by a facile and green Ce(iv )-redox process, to remove Pb 2+ from aqueous solutions. Abstract : A new adsorbent, sodium polyacrylate (PAANa) grafted onto the surface of bentonite (Bent), was successfully synthesized by a facile and green Ce(iv )-redox process, for the removal of Pb 2+ from aqueous solutions. The results indicate that by this method the original layered structure of the clay can be protected along with its cation exchange capability (CEC), leading to an improved adsorption capacity. The adsorbent (Bent–PAANa) was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectrometry (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA) and N2 adsorption–desorption isotherm studies. Subsequently the effects of pH, initial concentration and contact time on the adsorption of Pb 2+ from aqueous solutions were investigated. The results of the batch experiments specifically indicate that a high adsorption capacity (149.62 mg g −1 ) of Bent–PAANa for the removal of Pb 2+ was obtained at pH = 5, C 0 = 1100 mg L −1 and 25 °C. Furthermore, the adsorption kinetics of Pb 2+ onto the composite followed a pseudo-second-order kinetic model. The adsorption data fitted better to a Freundlich adsorption isotherm than a Langmuir adsorption isotherm hence confirming multilayer adsorption.